Bimbingan Pemanfaatan Waktu Luang di Masa Pandemi Bagi Ibu-Ibu Di RW 007 Kelurahan Sukajadi Kabupaten Banyuasin - Tri Rositasari; Dwi Rara Saraswaty; Finza Larasati; Kurnia Saputri; Dian Septarini; Nurhayati Dina; Andriamella Elfarissyah; Sri Yuliani; Sherly Marliasari (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2022)
Housewives who have a lot of activities in the household produce a lot of domestic (household) waste every day, both in the form of organic and inorganic waste. The role of housewives in managing household waste, especially organic waste, will be very beneficial for the environment. Therefore, this service activity is aimed at housewives in utilizing organic waste into liquid fertilizer that has economic value to help the hobbies or hobbies of housewives to maintain plants at home so that they become fertile without incurring additional costs and provide information on how to make healthy drink made from spices in the kitchen, which is useful for maintaining body stamina during this pandemic by utilizing free time at home. The purpose of this study was to find out how to process organic waste into liquid fertilizer, how to make healthy drinks from areca nut and garlic, and how to make healthy drinks from ginger and brown sugar. From this community service activity, it can be concluded that: (1) The knowledge and understanding of the community regarding the procedures for processing household waste and spices has increased. (2) Public awareness and desire to participate in creating a healthy environment and maintaining physical fitness during this pandemic has increased. Given the magnitude of the benefits of this community service activity, it is further necessary to: (1) Conduct similar socialization and outreach to communities in other sub-districts, with the same material. (2) There is a continuity of the program after this service activity so that the community really understands and realizes the importance of processing household waste and spices, in an effort to create a healthy environment and improve health in the community.